Respon Pertumbuhan Kultur In Vitro Jeruk Besar (Citrus maxima (Burm.) Merr.) cv. Nambangan terhadap Osmotikum dan Retardan - Iswari S. Dewi; Gani S. Jawak; Bambang S. Purwoko; M. Sabda (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2014)
ABSTRACTIn vitro conservation has been applied to many species. However, the suppression of explant growth is essential for extending the duration of conservation. The objective of the research was to study in vitro growth response of pummelo cv. Nambangan to conservation medium containing osmotically active compound (osmoticum) or growth suppressant (retardant). Two sets of experiments were conducted using randomized complete design and replicated three times. In vitro shoot with four leaves from pummelo, namely cultivar Nambangan, were used as the plant materials. The treatment in the first experiment was MS + osmoticum (mannitol 0, 20, 40, and 60 g L-1) and in the second experiment was MS + retardant (paclobutrazol 0, 1, 3 and 5 mg L-1). The resultsindicated that senescence of the leaf was induced by 20, 40, and 60 g L-1of mannitol. The best media in inhibition of growth for pummelo cv. Nambangan was MS + paclobutrazol 1 mg L-1. With this media, plant was inhibited but grew normally with green leaf and root.Keywords: mannitol, minimal growth, paclobutrazol, pummelo ABSTRAKKonservasi in vitro sudah banyak dilakukan pada berbagai spesies. Penghambatan pertumbuhansangat penting bagi lamanya tanaman dapat disimpan. Tujuan penelitian ini adalah mempelajari respon pertumbuhan in vitro pamelo cv. Nambangan terhadap media konservasi mengandung osmotikum atau penghambat pertumbuhan (retardan). Dua percobaan dilakukan terpisah menggunakan rancangan acak lengkap dan diulang 3 kali. Tunas hasil perbanyakan in vitro dengan 4 daun, digunakan sebagai eksplan. Perlakuan pada percobaan pertama adalah MS + osmotikum (mannitol 0, 20, 40, 60 g L-1) dan pada percobaan kedua adalah MS + retardan (paclobutrazol 0, 1, 3,5 mg L-1). Hasil menunjukkan bahwa daun mengalami senesen oleh perlakuan mannitol. Media yang direkomendasikan untuk konservasi pamelo cv. Nambangan adalah MS + paclobutrazol 1 mg L-1. Dengan media tersebut pertumbuhan dihambat, tetapi tetap normal, berakar dengan daun tetap hijau.Kata kunci: mannitol, pertumbuhan minimal, paclobutrazol, pamelo